Effects of exclusion on social preferences - Sven Fischer; Werner Güth (Max Planck Institute for Research on Collective Goods, 2011)
In three party ultimatum games the proposer can first decide whether to exclude one responder, what increases the available pie. The experiments control for intentionality of exclusion and veto power of the third party. We do not find evidence for indirect reciprocity of the remaining responder after exclusion of the other. Similarly, not excluding the second responder is only insignificantly reciprocated by him. Overall, we find little evidence that intentional exclusion affects response behavior.
Keywords: C91; J52; 330; experiment; social preferences; exclusion; bargaining; ultimatum game; Ultimatumspiel; Verhandlungstheorie; Soziale Wohlfahrtsfunktion; Austauschtheorie (Soziologie); Test